The Concept of a Zero Runoff System (ZROS) in reducing the volume of rainwater runoff using infiltration wells at the Syiah Kuala University - Ichwana Ramli; Suci Mutia; Fachruddin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
High rainfall with a very high intensity can cause inundation. The purpose of this study was to determine the magnitude of the designed flood discharge that occurred, and the number of infiltration wells needed to reduce rainwater runoff. This research uses data of maximum 10 years of daily rainfall for observation. The results showed that the rainfall intensity for the 5 years return period was 47.24 mm/hr resulting in a design flood discharge of 2.27 m3/second. The average well water level is 5.08 cm with an average soil permeability value of 5.03 cm/hour. Infiltration wells are designed with a depth of 1.5 m with a diameter of 1.4 m. The use of wells is calculated based on 2 types, type 1 (lined well walls) and type 2 (non-lined walls) in each roof class. The total area of roof covering 15.38 ha requires ± 2.678 type 1 wells, or ±2.440 type 2 wells which can reduce rainwater runoff by 17% (type 1) or 30% (type 2) of the total flood discharge of the Syiah Kuala University.